Gambaran Status Kesehatan Masyarakat RT 04 dan RT 07 Dusun Pringgolayan, Kecamatan Banguntapan, Kabupaten Bantul - Tyas Aisyah Putri; Aini Zahra; Asma Karimah; Reyna Maulidian (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Health is one of the most important needs in human life. The four main factors that affect the health status of the community are family genetics, environment, individual behavior, and health care facilities. Community diagnosis is important because it can identify broad issues and cover various aspects of the community such as culture, social structure, community roles, and so on. The purpose of this study was to determine the health status of the community at RT 04 and RT 07 in Pringgolayan Hamlet, Banguntapan District, Bantul Regency. This research is a research with a descriptive quantitative design with a purposive sampling method sampling technique with a total of 117 household heads (KK) respondents with data collection through interviews and door-to-door visits. The results of this study revealed that the public health status in RT 04 and RT 07 mostly implemented clean and healthy living behaviors. Conclusion: The public is aware of health behaviors that must be carried out in their daily activities, and health workers are expected to be even more active in conducting health education to the public.